2015
DOI: 10.1007/s10661-014-4210-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation behaviour of spinosad in polyhouse grown tomato under mid-hill conditions of Himachal Pradesh, India

Abstract: An established analytical method was further standardized for the estimation of spinosad residue in tomato grown under naturally ventilated polyhouse situated in mid-hills of Himachal Pradesh, India. Spinosad was sprayed on hybrid tomato cv. Avtar at the recommended and double the recommended dosages at 15 and 30 g a.i. ha(-1), respectively, to control the lepidopterous pests and the residue were analysed from tomato fruits at different intervals after second spray. The samples were extracted with acetonitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…The results of spinosad residue analysis are in consistent with those obtained by Kashyap et al (2015), who reported that half-life values of spinosad were determined to be 1.20 and 1.60 d at recommended and double the recommended dosage, respectively. The safety interval for spinosad sprayed tomato fruit was determined to be 1.92 and 3.88 d at application rate of 15 and 30 g ai ha -1 , respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The results of spinosad residue analysis are in consistent with those obtained by Kashyap et al (2015), who reported that half-life values of spinosad were determined to be 1.20 and 1.60 d at recommended and double the recommended dosage, respectively. The safety interval for spinosad sprayed tomato fruit was determined to be 1.92 and 3.88 d at application rate of 15 and 30 g ai ha -1 , respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Recoveries were between 85% and 130% at two fortified levels. (Kashyap and Sharma, 2015) estimated spinosad residue in tomato planted in India, and they found that the half-life time of spinosad was 1.20 days. The safety interval was 1.92 days.…”
Section: B Spinosad Residuesmentioning
confidence: 99%